2022
DOI: 10.1001/jamanetworkopen.2022.6567
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Alzheimer Disease and Related Dementia Among Medicare Beneficiaries With Rheumatoid Arthritis Treated With Targeted Disease-Modifying Antirheumatic Agents

Abstract: IMPORTANCECytokine signaling, including tumor necrosis factor (TNF) and interleukin (IL)-6, through the Janus-kinase (JAK)-signal transducer and activator of transcription pathway, was hypothesized to attenuate the risk of Alzheimer disease and related dementia (ADRD) in the Drug Repurposing for Effective Alzheimer Medicines (DREAM) initiative based on multiomics phenotyping. OBJECTIVE To evaluate the association between treatment with tofacitinib, tocilizumab, or TNF inhibitors compared with abatacept and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Extending our recent work examining candidate AD treatments targeting the JAK/STAT cytokine signaling pathway [3,9], we now demonstrate that HCQ lowers the incidence of ADRD compared to MTX in older individuals, rescues impaired hippocampal synaptic plasticity in APP/PS1 mice and corrects multiple molecular abnormalities underlying AD. Together, these findings suggest that HCQ may be a promising disease-modifying AD treatment in at-risk individuals.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Extending our recent work examining candidate AD treatments targeting the JAK/STAT cytokine signaling pathway [3,9], we now demonstrate that HCQ lowers the incidence of ADRD compared to MTX in older individuals, rescues impaired hippocampal synaptic plasticity in APP/PS1 mice and corrects multiple molecular abnormalities underlying AD. Together, these findings suggest that HCQ may be a promising disease-modifying AD treatment in at-risk individuals.…”
Section: Discussionmentioning
confidence: 56%
“…Prior studies have suggested that dysregulation in this pathway may be associated with neurodegenerative diseases [4,5] and may therefore may be a plausible therapeutic target [6][7][8]. We recently showed that disease modifying antirheumatic drugs (DMARDs) including tofacitinib (a JAK inhibitor), and 2) tocilizumab (an interleukin [IL]-6 inhibitor) were not associated with risk of AD and related dementias (ADRD) while TNF inhibitors may reduce risk of ADRD among patients with cardiovascular disease [9]. We additionally showed that C188-9, an experimental STAT3 inactivator currently in human clinical trials of cancer, rescued several molecular phenotypes relevant to AD in cell culture-based phenotypic assays [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical research has applied this definition to ascertain ADRD among persons for whom this diagnosis has important prognostic and treatment-related implications for comorbid conditions, such as cancer 3. Emerging applications of claims-based ADRD ascertainment now include drug-repurposing and pharmacogenomics 4…”
Section: Festa and Colleagues Highlight Under-recognised Factors That...mentioning
confidence: 99%
“…Two recent studies from the US and UK showed a reduced risk of dementia with the use of biologics in RA patients (46) (47). A recent large cohort study using propensity-score matching did not find any difference in the risk of dementia in patients with RA treated with TNFi, IL-6 inhibitor or Janus kinase inhibitor versus abatacept, although patients were followed up for a maximum of only 3 years (48). In our study, we did not find an association between exposure to DMARDs at any time during the follow-up (i.e., "ever use") and incident dementia.…”
Section: Examining Temporal Associations Between Cvd Risk Factors On ...mentioning
confidence: 99%